Role of inflammatory cytokines and the gut microbiome in vascular dementia: insights from Mendelian randomization analysis - Yang, Yihan; Rao, Ting; Wei, Sheng; Cheng, Jing; Zhan, Ying; Lin, Teng; Chen, Jincheng; Zhong, Xiaoling; Jiang, Yijing; Yang, Shanli (Frontiers in Microbiology, 2024)
This Mendelian randomization (MR) study identified the inflammatory cytokines and gut microbiome members that influence the risk of developing VaD and their causal effects, and investigated whether inflammatory cytokines are gut microbiome mediators affecting VaD. We obtained pooled genome-wide association study (GWAS) data for 196 gut microbiota and 41 inflammatory cytokines and used GWAS data for six VaD subtypes, namely, VaD (mixed), VaD (multiple infarctions), VaD (other), VaD (subcortical), VaD (sudden onset), and VaD (undefined). We used the inverse variance-weighted (IVW) method as the primary MR analysis method. We used multivariable MR (MVMR) analysis to assess the direct causal effects of inflammatory cytokines and the gut microbiome on the risk of VaD, and performed mediation MR analysis to explore whether inflammatory factors were potential mediators. Our two-sample MR study revealed relationships between the risk of 6 VaD subtypes and inflammatory cytokines and the gut microbiota: 7 inflammatory cytokines and 14 gut microbiota constituents were positively correlated with increased VaD subtype risk, while 2 inflammatory cytokines and 11 gut microbiota constituents were negatively correlated with decreased VaD subtype risk. After Bonferroni correction, interleukin-18 was correlated with an increased risk of VaD (multiple infarctions); macrophage migration inhibitory factor was correlated with an increased risk of VaD (sudden onset); interleukin-4 was correlated with a decreased risk of VaD (other); Ruminiclostridium6 and Bacillales were positively and negatively correlated with the risk of VaD (undefined), respectively; Negativicutes and Selenomonadales were correlated with a decreased risk of VaD (mixed); and Melainabacteria was correlated with an increased risk of VaD (multiple infarctions). Sensitivity analyses revealed no multilevel effects or heterogeneity and no inverse causality between VaD and inflammatory cytokines or the gut microbiota. The MVMR results further confirmed that the causal effects of Negativicutes, Selenomonadales, and Melainabacteria on VaD remain significant. Mediation MR analysis showed that inflammatory cytokines were not potential mediators. This study helps us to better understand the pathological mechanisms of VaD and suggests the potential value of targeting increases or decreases in inflammatory cytokines and gut microbiome members for VaD prevention and intervention.